Japanese temple Buddhism: worldliness in a religion of renunciation - Amstutz, Galen Dean (Japanese religions, 2006)
Review of Covell, Stephen G. Japanese temple Buddhism: worldliness in a religion of renunciation. Publisher: Honolulu : Univ of Hawai'i Pr, 2005